1982
DOI: 10.1677/joe.0.0940397
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a photoinducible phase for the release of luteinizing hormone in the domestic hen

Abstract: Hens raised on a schedule of 8 h light : 16 h darkness (8L : 16D) were exposed to changes in photoperiod at 17 or 18 weeks of age. These involved exposure to either an abrupt increase in photoperiod to 16 h per day or to skeleton photoperiods comprising a main period of 7\m=.\75or 4 h light together with a pulse of 15 min or 4 h light provided at different times during the period of darkness.An increase in photoperiod to 16 h per day stimulated a two-to threefold increase in the plasma concentration of LH with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Morris (1978) suggested that the extra effectiveness of relatively short light periods in ahemeral cycles is caused by the fact that, every 'afternoon', new hours are lighted. This interpretation is in accordance with the well-accepted idea of a photo-inducible phase located approximately 11 to 16 h after dawn (Follett and Sharp, 1969;Follett, 1973;Siopes and Wilson, 1980;Wilson, 1982). These researchers have shown that light which falls within these sensitive hours will stimulate reproductive function.…”
Section: Melatonin Rhythmsupporting
confidence: 88%
“…Morris (1978) suggested that the extra effectiveness of relatively short light periods in ahemeral cycles is caused by the fact that, every 'afternoon', new hours are lighted. This interpretation is in accordance with the well-accepted idea of a photo-inducible phase located approximately 11 to 16 h after dawn (Follett and Sharp, 1969;Follett, 1973;Siopes and Wilson, 1980;Wilson, 1982). These researchers have shown that light which falls within these sensitive hours will stimulate reproductive function.…”
Section: Melatonin Rhythmsupporting
confidence: 88%
“…As a consequence, the delaying effect of the decrease more or less cancels out the stimulatory influence of the increase. It is speculated that this is because the increased concentrations of circulating gonadotrophin that would undoubtedly have resulted from the increment in photoperiod (Wilson, 1982;Lewis et al, 1994Lewis et al, , 1999, were subsequently suppressed or curtailed by the decrease in daylength (Urbanski and Follett, 1982;Lewis et al, 1998), and that this slowed, but did not prevent, sexual maturation. Unfortunately, plasma gonadotrophin concentrations were not measured in this experiment, so this proposal cannot be substantiated.…”
Section: Discussionmentioning
confidence: 99%
“…Although two-to three-fold increases in plasma LH were observed in 17-week-old domestic pullets within 1-3 d of a transfer from 8-to 16-h photoperiods (Wilson, 1982), and significant increases in plasma LH, and ovarian and oviducal weights were recorded in dwarf broiler breeders 14 d after they had been transferred from 8-to 20-h photoperiods , no advance in age at first egg (AFE) occurred when pullets were temporarily transferred from 8 h to 10, 12, 14 or 16 h for 1 or 2 d at various ages between 10 and 16 weeks of age (Lewis and Gous, 2004).…”
Section: Introductionmentioning
confidence: 87%
“…1). This is in marked contrast to luteinizing hormone (LH), which shows a two- to three-fold rise in plasma concentration within 1–3 days of pullets being transferred to a stimulatory daylength (Wilson 1982). However, circulating LH concentrations are poorly correlated with rate of sexual development in pullets (Lewis et al 1994).…”
mentioning
confidence: 98%